الشعر في موقعة صفين - أحمد, عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول هذا البحث بالدراسة الشعر الذي قيل في موقعة صفّين، ويحاول أن يبيّن الدور الذي أداه هذا الشعر في التعبير عن المواقف والأحداث التي جرت في هذه المعركة. كما يحاول أن يبيّن الأفكار والآراء التي عبّر عنها شعراء كل طرف من الطرفين المتحاربين، ثم الدور الذي أدّاه الشعراء في التحريض على القتال، وسيكون هذا من خلال الوقوف على تحرض "القائد" و"المقاتلين" و"الذّات". ثم سيحاول البحث الوقوف عند أبرز الأغراض الشعرية الأخرى التي تناولها الشعراء في المعركة وهي الرثاء والفخر. ولا ينسى البحث أن يصغي – على الرغم من ضجيج المعركة- إلى بعض أصوات راحت تتحدث عن مرارة ما يجري معبرة بذلك عن وعي مثير للاهتمام يستحق التأمل فيه. This piece of research highlights the poetry that had been said during the Battle of Siffen. It attempts to make clear the role that poetry had played in expressing the stands and events that took place within the course of this battle. It also tries to disclose the opinions and thoughts that were spelt out by the poets of each of the two conflicting parties. Moreover, it endeavours to manifest the role of the poets in providing soldiers with a stimulus for fighting, as had been apparent through focusing on stimulating the "leader", "soldiers" and the poets "themselves". Afterwards, it attempts to draw attention to the other most dominant kinds of poetry that poets got indulged with during wartime: elegy and pride. Notwithstanding the great noise caused by the battle, this piece of research does not neglect the moments during which it could hardly be possible to listen to some voices that were portraying the awful details of what was going on, henceforward revealing an increasingly interesting awareness that has proved worthy of attention.